Anthropomorphic profile of masters competitive Olympic weightlifters - Hatchett, Andrew; Helms, Matthew; Grieve, George; Hatchett, Iris; Huebner, Marianne; Riemann, Bryan; Wolford, Dillon; Rodriguez, Abelardo (Journal of Sports Research, 2025)
The masters athlete is typically defined as older than 35 years who either trains for or takes part in athletic competitions often specifically designed for older participants. Masters athletes provide a unique research cohort to understand the role of regular vigorous exercise in optimizing physical potential and health with advancing age. Olympic weightlifting is a sport that demands specific physical attributes and rigorous training to excel. Anthropomorphic and competition data were collected for male and female athletes competing at the 2022 World Master Weightlifting Championships. Of the 820 eligible athletes, 172 from 17 countries participated in the physical assessment of the study. Female participants were slightly taller when compared to the general public and males shorter. Participants, both female and male, presented lower body mass index scores and waist circumference measures. Understanding the physical profiles of Masters athletes provides valuable insights for considering the impact of Olympic weightlifting. Masters Olympic weightlifters present physical profiles of aging with a functional capacity greater than that of an age-matched general population.